MODELING AND SIMULATION OF PROXIMITY SENSORS - SORIN EUGEN POPA (Journal of Engineering Studies and Research)
In the context of the pandemic caused by the COVID-19 virus, the transition to online education was forced. Also, the laboratory works from the engineering disciplines must be adapted to the online environment. This paper presents the study of infrared proximity sensors, raising the operating characteristic and comparing it with that provided by the sensor manufacturer. The transfer function of the sensor will be determined annalistically and will be compared with the one obtained from the simulation. At the end, the conclusions we can draw will be presented.